Una nueva especie de Chaunanthus (Cruciferae) endémica de Querétaro, México - Martínez, Mahinda; Hernández-Sandoval, Luis (Instituto de Ecología, A.C., 2007)
We describe a new species of Chaunanthus, a small genus of white flowered suffrutescent plants endemic to Mexico. The new species differs from the others because it is glabrous throughout, has winged petioles, and bilobed stigma, with erect lobes.